The Anti-Inflammatory Effect of Chenopodium Murale in Comparison to Salvia Frigida on Atopic Eczema - Zahraa Y. Hassan; Tuka Y. Hassan; Ahmed Y. Kanany (مجلة كلية الطب)
Background: Atopic dermatitis (AD) is a prevalent chronic inflammatory skin condition with a familial tendency. It affects approximately 10%-20% of children and 1%-3% of adults worldwide. Chenopodium murale is clinically proven for treating many medical conditions, such as AD, due to its easy application and efficacy. Salvia plant has an anti-inflammatory effect on AD cases treated with phenolic compounds.